Permintaan uang di Indonesia tahun 1976-1996 (Konsep keynesian dan monetaris dengan pendekatan PAM) - Nano Prawoto (Economic Journal of Emerging Markets, 2000)
Demand for money is one of the large-scale monetary that plays an important role in the behavior of monetary policy in every economy. The monetary policy can give a contribution to reach the economy.